Occupational lead exposure in Finland. VI. Final report. - Tola, Sakari; Hernberg, Sven; Vesanto, Ritva (Scandinavian Journal of Work, Environment & Health, 1976)
Between 1970 and 1973, 2,209 workers representing 30 different types of work were studied in Finland for lead exposure. The indicator of lead exposure was the blood lead concentrations (Pb-B) of the workers. The highest recommended value for Pb-B in Finland, 70 mug/100 ml of blood, was exceeded in the following types of work: PVC plastic manufacturing, storage tank manufacturing and repairing, machine shop work, treating metal surfaces, paint manufacturing, car radiator repairing, spray painting, machine shop work (railway), and storage battery repair. The types of work with the highest average exposure were lead scrap smelting (Pb-B median 79 mug/100 ml, range 35--118), storage battery manufacturing (Pb-B median 66 mug/100 ml, range 19--101), metal founding, (Pb-B median 53 mug/100 ml, range 6--108) shipbreaking (Pb-B median 49 mug/100 ml, range 26--106) crystal glass manufacturing (Pb-B median 41 mug/100 ml, range 12--82), car radiator repairing (Pb-B median 38 mug/100 ml, range 17--83), and PVC plastic manufacturing (Pb-B median 37 mug/100 ml, range 10--126). During the past 5 years cases of clincial lead poisoning have occurred in all of these types of work, and the patients received workmen's compensation. The usefulness of the national poisoning register in predicting the relative hazard of lead exposure in the types of work studied was evaluated with the aid of rank order correlation statistics. The analysis showed that the poisoning register is a useful indicator of lead exposure in the most exposed types of work. However, the present survey also revealed work in which the hazard had escaped recognition in this country: metal founding, car repairing, and car radiator repairing, for example. Although it seems possible to predict the most heavily exposed work types from national poisoning registers only, the detection of workers with less severe manifestations of toxic effects, or somtimes even poisoning, in other types of work first requires a systematic survey of all types of work with possible lead exposure, and then regular monitoring of all exposed workers.
Keywords: blood lead; exposure; Finland; lead; lead exposure; lead work; occupational lead exposure; occupational medicine